Bubba and Beau meet the relatives - Appelt, Kathi; Howard, Arthur (Orlando : Harcourt, 2004)
While preparing for a visit from some relatives--and even after they arrive--Bubba and Beau want nothing more than to sink their paws into the squishy, squashy mud hole.
89452
Keywords: Hospitality -- Fiction; Mud -- Fiction; Dogs -- Fiction; Hospitality -- Juvenile fiction; Mud -- Juvenile fiction; Dogs -- Juvenile fiction